Reverse shoulder arthroplasty: Short to mid-term clinical and radiological results (Annals of Medical Research, 2022)
Aim: This paper aimed to review the early and midterm radiological and clinical findings of our patients who were treated surgically with reverse shoulder prosthesis via to rotator cuff arthropathy.Materials and Methods: A total of 22 patients (female: 14, male 8), with shoulder arthrosis due to cuff tears were treated with reverse shoulder prosthesis between 2015 and 2018 in our clinic. The mean age of the patients was detected as 69.4 years (65-93 years). The mean clinical follow-up was detected as 11 months (3-36 month). The patients were evaluated with Visual Analog Scale (VAS), Shoulder Constant Score, American Shoulder/Elbow Surgeons Shoulder Score (ASES) scores, preoperatively. In last outpatient visits, patients were evaluated with radiological views and range of motion, Shoulder Constant, VAS and ASES scores.Results: The mean shoulder flexion, extension, and abduction was measured as 101°, 24°, and 97.9° respectively in the last polyclinic controls. The mean shoulder Constant scores were 30.8 preoperatively and 62.1 at follow-up (p=0.001). Preoperatively, the mean score of ASES was 31.6.  And it was increased to 65.9 with the last follow-up (p=0.001). The mean preoperative VAS scores were 7.42, and the mean postoperative mean were 2.8 (p=0.001). Periprosthetic fracture developed intraoperatively in one patient who also had a dislocation occurred in the 2nd month postoperatively. In another patient, superficial infection occurred at the postoperative 3rd week. One patient died because of cardiac problems postoperatively and another one had a traumatic periprosthetic fracture at 5th month postoperatively.  Conclusion: While clinical presentation of patient is an advanced rotator cuff tear arthropathy, the application of reverse shoulder prosthesis is major surgical procedure. Also, with appropriate rehabilitation protocol, significant improvement in pain and function can be achieved.
Keywords: Reverse shoulder prosthesis; rotator cuff tear arthropathy; radiological results